2014
DOI: 10.1075/intp.16.1.04gal
|View full text |Cite
|
Sign up to set email alerts
|

Orality and authenticity in an interpreter-mediated defendant’s examination

Abstract: This case study examines how a court's perception of the defendant's socio-legal identity may be affected by interpreting. Since this perception relies largely on language, interpreters are expected to minimise their impact on the dynamics of direct communication between primary participants. The analysis focuses on an interpreter-mediated defendant's examination, recorded in an attempted murder case tried before the Belgian Assize Court, identifying possible departures from the principles of orality and authe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Ces stratégies reflètent l'ajustement en fonction du récepteur (recipient design, Goodwin 1981 : 149-166) et l'orientation en fonction des objectifs (Heritage & Drew 1992), caractéristiques des conversations institutionnelles. De telles stratégies sont typiques dans l'interprétation des entretiens d'asile (Pöllabauer 2004 : 154 ;Gallez & Maryns 2014 ;Määttä 2015 ;Puumala, Ylikomi & Ristimäki 2018 : 206-207). En d'autres mots, l'interprète sait que l'enquêteur préfère utiliser un nom de métier pour décrire l'activité professionnelle du demandeur dans le procèsverbal, d'un côté, et sait que le demandeur comprend plus facilement une description du processus dans lequel on utilise les mêmes verbes dont il s'est servi dans sa réponse (lignes 1, 2 et 4), d'un autre côté.…”
Section: Exemple (4)unclassified
“…Ces stratégies reflètent l'ajustement en fonction du récepteur (recipient design, Goodwin 1981 : 149-166) et l'orientation en fonction des objectifs (Heritage & Drew 1992), caractéristiques des conversations institutionnelles. De telles stratégies sont typiques dans l'interprétation des entretiens d'asile (Pöllabauer 2004 : 154 ;Gallez & Maryns 2014 ;Määttä 2015 ;Puumala, Ylikomi & Ristimäki 2018 : 206-207). En d'autres mots, l'interprète sait que l'enquêteur préfère utiliser un nom de métier pour décrire l'activité professionnelle du demandeur dans le procèsverbal, d'un côté, et sait que le demandeur comprend plus facilement une description du processus dans lequel on utilise les mêmes verbes dont il s'est servi dans sa réponse (lignes 1, 2 et 4), d'un autre côté.…”
Section: Exemple (4)unclassified
“…While there are studies about the ways in which such alterations happen and the kind of alterations that may occur in interpreter-mediated interviews (e.g. Gallez & Maryns, 2014;Jacquemet, 2009;Pöllabauer, 2004), it is also useful to reflect on the reasons why these alterations take place. This will be the main theme of the next section.…”
Section: The Discourse Of Reporting In Interpreter-mediated Police Inmentioning
confidence: 99%
“…As studies on literary translation of sociolinguistic variation have shown (Määttä, 2004), it is impossible to find exact equivalences between non-normalized varieties and idiolects in two different languages, for the ideological constellations and cultural connotations of such varieties can never be the same in two different cultures and contexts. Therefore, it is inevitable that phenomena such as "styles" or "authentic features" (Gallez & Maryns, 2014) are altered in the process of interpretation and transcription. Similarly, it is impossible to interpret incoherent, spontaneous oral speech accuratelyeven in simultaneous interpreting with headphones and microphones this would be quite difficult.…”
Section: The Discourse Of Reporting As a Normalizing Device Explaininmentioning
confidence: 99%
“…The more we know from different traditions across languages, cultures, and time, the more undeniable the diversity of coexisting definitions of LIT and its core notions becomes. A new zeitgeist is advancing ethnographic studies (Valdés et al 2000, Inghilleri 2003, Koskinen 2008, Gallez/Maryns 2014, which present human experience as fragmented and provide specific cases and systematically taken data for a context-dependent discussion. "The turn to ethnography promises greater attention to agency and a focus on non-discursive practices and the potential of resistance to discourses otherwise seen as totalizing and reductionist to individual freedom. "…”
Section: Introductionmentioning
confidence: 99%